Robotic Advisors, Risk Tolerance, and Trust: Their Impact on Sharia-Compliant Investment Decisions in Fintech Applications (A Study of Generation Z Retail Investors in Jakarta) - Hendi Yudhanto Adinugroho (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2025)
The development of Financial Technology has transformed individual investment behavior, particularly through Robo Advisors, which leverage algorithms and Artificial Intelligence to provide automated, efficient, and risk profile aligned investment recommendations. This study examines the influence of Robo-Advisors, risk tolerance, and trust levels on Sharia mutual fund investment decisions among Generation Z investors in Jakarta. The data for this research were collected between June 2025 and July 2025. The research employs a descriptive quantitative approach with a sample of 105 Generation Z investors selected through purposive sampling. Data were collected using questionnaires and analyzed using multiple linear regression, including determination tests, F-tests, and T-tests. The results indicate that Robo-Advisors (β = 0.183), risk tolerance (β = 0.276), and trust (β = 0.492) have positive and significant effects on Sharia mutual fund investment decisions, with trust being the dominant factor. Together, these three variables explain 62.8% of the variation in investment decisions. The findings confirm that the integration of technological innovation, psychological characteristics, and trust perception constitutes the main determinants of Generation Z investment behavior, providing both academic contributions and practical implications for the development of digital investment platforms. Practically, platforms targeting Generation Z must prioritize building trust through enhanced data security and transparency, as well as providing personalized risk education tools, so that adoption increases and perceived investment risk decreases.